Essential oils as promising treatments for treating Candida albicans infections: research progress, mechanisms, and clinical applications - Hou, Gao-wei; Huang, Ting (Frontiers in Pharmacology, 2024)
Candida albicans (C. albicans) is a prevalent opportunistic pathogen that can cause severe mucosal and systemic fungal infections, leading to high morbidity and mortality rates. Traditional chemical drug treatments for C. albicans infection have limitations, including the potential for the development of drug resistance. Essential oils, which are secondary metabolites extracted from plants, have gained significant attention due to their antibacterial activity and intestinal regulatory effects. It makes them an ideal focus for eco-friendly antifungal research. This review was aimed to comprehensively evaluate the research progress, mechanisms, and clinical application prospects of essential oils in treating C. albicans infections through their antibacterial and intestinal regulatory effects. We delve into how essential oils exert antibacterial effects against C. albicans infections through these effects and provide a comprehensive analysis of related experimental studies and clinical trials. Additionally, we offer insights into the future application prospects of essential oils in antifungal therapy, aiming to provide new ideas and methods for the development of safer and more effective antifungal drugs. Through a systematic literature review and data analysis, we hope to provide insights supporting the application of essential oils in antifungal therapy while also contributing to the research and development of natural medicines. In the face of increasingly severe fungal infections, essential oils might emerge as a potent method in our arsenal, aiding in the effective protection of human and animal health.